Investigations on the Blade Vibration of a Radial Inflow Micro Gas Turbine Wheel - Shijie Guo (International Journal of Rotating Machinery)
This paper demonstrates the investigations on the blade vibration of a radial inflow micro gas turbine wheel. Firstly, the dependence of Young's modulus on temperature was measured since it is a major concern in structure analysis. It is demonstrated that Young's modulus depends on temperature greatly and the dependence should be considered in vibration analysis, but the temperature gradient from the leading edge to the trailing edge of a blade can be ignored by applying the mean temperature. Secondly, turbine blades suffer many excitations during operation, such as pressure fluctuations (unsteady aerodynamic forces), torque fluctuations, and so forth. Meanwhile, they have many kinds of vibration modes, typical ones being blade-hub (disk) coupled modes and blade-shaft (torsional, longitudinal) coupled modes. Model experiments and FEM analysis were conducted to study the coupled vibrations and to identify the modes which are more likely to be excited. The results show that torque fluctuations and uniform pressure fluctuations are more likely to excite resonance of blade-shaft (torsional, longitudinal) coupled modes. Impact excitations and propagating pressure fluctuations are more likely to excite blade-hub (disk) coupled modes.